Analisis Bentuk dan Makna Lagu Tondi Tondikku Karya Herbet Aruan yang Dinyanyikan Style Voice - Elvita Uli Purba; Emmi Simangunsong; Kamalluddin Sigalingging (FBS Universitas Negeri Padang, 2022)
This article discusses the analysis of the form and meaning of the song Tondi Tondikku by Herbet Aruan which is sung by Style Voice. The method used in this research is descriptive qualitative method. The song Tondi Tondikku was composed in 2019 by Herbet Aruan and sung by Style Voice. The results obtained in this study are the song Tondi Tondikku has an intro, main melody and ending. Tondi Tondikku's song was performed with piano instruments, soprano saxophone, electric guitar, bass guitar, drums, violin with 4/4 rhythm and with adagio tempo. Tondi Tondikku's song is Binary Form which is a two-part song form. The song Tondi Tondikku has a deep meaning for parents. The meaning contained in the song Tondi Tondikku tells about the expression of feelings of love and affection of parents for their children and illustrates that the father is the first man seen by his daughter and he is the first to lose his daughter if he later finds a mate and lives with his husband